Small RNA Based Genetic Engineering for Plant Viral Resistance: Application in Crop Protection - Khalid, Annum; Zhang, Qingling; Yasir, Muhammad; Li, Feng (Frontiers in Microbiology, 2017)
Small RNAs regulate a large set of gene expression in all plants and constitute a natural immunity against viruses. Small RNA based genetic engineering (SRGE) technology had been explored for crop protection against viruses for nearly thirty years. Viral resistance has been developed in diverse crops with SRGE technology and a few viral resistant crops have been approved for commercial release. In this review we summarized the efforts generating viral resistance with SRGE in different crops, analyzed the evolution of the technology, its efficacy in different crops for different viruses and its application status in different crops. The challenge and potential solution for application of SRGE in crop protection are also discussed.